ANALYSIS OF THE EFFECT OF LOAD IMBALANCE ON NEUTRAL CURRENT AND POWER LOSSES IN DISTRIBUTION TRANSFORMER BGLWY1036 SUBSTATION RUMAH TIGA - HAMLES LEONARDO LATUPEIRISSA; GILBERTH VALENTINO TITALEY (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Load imbalance in an electric power distribution system always occurs and the cause of this imbalance is single-phase loads on low-voltage network customers. As a result of the load imbalance, a current appears in the neutral of the transformer. The current flowing in the neutral of the transformer causes losses, namely losses due to neutral currents in the neutral conductor of the transformer and losses due to neutral currents flowing to the ground. The additional load on the BGLWY1036 distribution substation in Rumah Tiga village in a period of ± 2 years (2020-2022 which is significant without taking into account the distribution of the transformer load, the impact is felt for consumers, resulting in very large voltage and power losses. Data from measurements during the day and night day (peak load) carried out at the BGLWY1036 distribution substation in Rumah Tiga village, it can be seen that the magnitude of the voltage (V) and current (I), as well as the results of the apparent power calculation (S) are not the same in each phase (L1, L2 and L3). Based on the results of the analysis, the effect of load imbalance on neutral currents and power losses in the distribution transformer BGLWY1036 Rumah Tiga is obtained (i) power losses due to currents in the neutral conductor (PN) during the day by 8.650% and at night by 10.405 %. (ii) power losses due to neutral current flowing to the ground (PG) during the day is 1.201% and at night is 1.564%.